Pengembangan “RPP Generator” Menggunakan Metode Text Mining Untuk Meningkatkan Keterampilan Guru SMK Dalam Menyusun RPP K-13 - Eko Subiyantoro (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2019)
Based on Permendikbud Number 22 two thousand and sixteen, it is stated that every teacher in the education unit is obliged to prepare a Learning Implementation Plan (RPP) in a complete and systematic manner. So that each teacher is required to prepare and prepare an integrated and integrative Learning Implementation Plan. Unfortunately, not a few teachers have difficulties in determining the RPP model that really fits the needs of students. This study offers a software application that is able to analyze Basic Competencies (KD), matching suitable learning models, and integrating in the RPP format in accordance with the applicable provisions. Text mining methods are used to analyze the linearity of KD3 - KD4 and recommendations for learning models based on Operational Words (Revised Bloom's Taxonomy KKO, Dave-Simpson). While the application development model uses the Analysis, Design, Develop, Implement, and Evaluation (ADDIE) development methods that are integrated with the prototype development model at the design stage. The results of this study produce desktop-based RPP Generator software that can assist teachers in preparing K-13 lesson plans. The feasibility testing of this software includes the testing of material experts, media experts, and teachers obtained percentages with an average of 95.8%, thus the RPP Generator software can be used by teachers in making systematic K-13 RPP.